PENGARUH STRESS KERJA, GAYA KEPEMIMPINAN, DAN PENGALAMAN KERJA TERHADAP KINERJA AUDITOR DENGAN REKAN KERJASEBAGAI VARIABEL MODERATING (Studi Empiris pada KAP Padang, Pekanbaru, Medan, dan Batam) - Elsya Audita; Zirman Zirman; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the effect of work stress, leadership style, and work experience on auditor performance with working partner as moderating variable on Public Accounting Firm in Padang, Pekanbaru, Medan, and Batam.The methods used in this research was multiple linear regression. The sampling methods used was purposive sampling which counted 36 in 2016. Data collected by distributing questionnairs to 243 auditors working in 36 Public Accounting Firm, but only 178 questionnaires were returned and can be processed. The results of the hypothesis test showed that work stress, leadership style, and working experience has an effect on auditors performance with 0.001, 0.015, and 0.004 significance. Work stress, leadership style, and working experience that moderated by co-workers has an effect on auditors performance with 0.003, 0.029, and 0.014 significance.Keywords : work stress, leadership style, working experience, co-workers, auditors performance